Accountability of Population Administration Services at the Tamalanrea District Office, Makassar City - Onasis, Andi; Rifdan, Rifdan; Haerul, Haerul (Jurnal Office, 2023)
Accountability of Population Administration Services in Tamalanrea District, Makassar City aims to find out how Accountability of population administration is in the Tamalanrea sub-district office, Makassar city. This type of research is descriptive qualitative research. Data collection techniques are carried out through observation, interviews and documentation. The data analysis techniques used consist of data reduction, data presentation, and drawing conclusions. The results of this study show that the accountability of population administration at the Tamalanrea sub-district office in Makassar city in its implementation can be assessed based on each indicator, namely Legitimacy for policy makers, The existence of adequate moral quality, Sensitivity, Openness, Optimum utilization of resources and Efforts to increase efficiency and effectiveness therefore it is necessary to make improvements for the implementation of population administration services in Tamalanrea District, Makassar City.